2014
DOI: 10.1007/s00392-014-0791-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impact of a new left bundle branch block following TAVI implantation: 1-year results of the TAVIK cohort

Abstract: This study demonstrated that persistent new-onset LBBB was associated with increased mortality in patients undergoing TAVI. Compared with the Edwards SAPIEN valve, implantation of the Medtronic CoreValve resulted in a higher rate of both persistent new-onset LBBB and PM but not death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 104 publications
(67 citation statements)
references
References 42 publications
0
61
0
1
Order By: Relevance
“…The center of the diamond represents the point estimate, and the width represents 95% confidence interval (CI). Studies included in these analyses are Fadahunsi et al, 12 Dizon et al, 13 Biner et al, 14 D'Ancona et al, 23 De Carlo et al, 24 Houthuizen et al, 25 Buellesfeld et al, 26 Van Mieghem et al, 28 Pereira et al, 30 Schymik et al, 32 Maan et al, 33 Kostopoulou et al, 34 Mouillet et al, 35 Engborg et al, 36 and Kawaguchi et al 37 …”
Section: Study Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The center of the diamond represents the point estimate, and the width represents 95% confidence interval (CI). Studies included in these analyses are Fadahunsi et al, 12 Dizon et al, 13 Biner et al, 14 D'Ancona et al, 23 De Carlo et al, 24 Houthuizen et al, 25 Buellesfeld et al, 26 Van Mieghem et al, 28 Pereira et al, 30 Schymik et al, 32 Maan et al, 33 Kostopoulou et al, 34 Mouillet et al, 35 Engborg et al, 36 and Kawaguchi et al 37 …”
Section: Study Analysismentioning
confidence: 99%
“…In addition, for calculation of improvement in LVEF, there were 3 studies 16,17,21 where SDs for change (improvement) in LVEF were not available. Here, we imputed the SD based on other studies in the meta-analysis with similar follow-up duration based on guidelines 12 Dizon et al, 13 Biner et al, 14 D'Ancona et al, 23 De Carlo et al, 24 Houthuizen et al, 25 Buellesfeld et al, 26 Van Mieghem et al, 28 Pereira et al, 30 Schymik et al, 32 Maan et al, 33 Kostopoulou et al, 34 Mouillet et al, 35 Engborg et al, 36 and Kawaguchi et al 37 CI indicates confidence interval; MH, Mantel-Haenszel; and PPM, permanent pacemaker. Impact of Post-TAVR Pacemaker for systematic reviews provided by the Cochrane Collaboration.…”
Section: Study Analysismentioning
confidence: 99%
“…The diagnosis criteria for LBBB were based on the recommendations from the American Heart Association/American College of Cardiology Foundation/Heart Rhythm Society 20 in 4 studies 3,4,13,18 and from the World Health Organizational/International Society and Federation for Cardiology 21 in 2 studies. 11,19 One study 12 did not detail the diagnosis criteria. The study-selection process is shown in Figure 1.…”
Section: Search Resultsmentioning
confidence: 99%
“…High heterogeneity was observed (I 2 = 83%, P = 0.001). Self-expandable balloon was a risk of both NOP-LBBB and PPI, 11,18 and we consider that the significant heterogeneity is mainly because the implanted prosthesis differs considerably among studies, as summarized in the Table 1. The main risks for PPI after TAVI include preexistent right bundle branch block, self-expandable prosthesis valve, and depth of implantation.…”
Section: Permanent Pacemaker Implantation In New-onset Persistent Lefmentioning
confidence: 99%
See 1 more Smart Citation